2021
DOI: 10.1088/1742-6596/2084/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Age Group Classification using Convolutional Neural Network (CNN)

Abstract: Age group classification is a complex task that is used to classify facial images or videos into predetermined age categories. It is an important task due to its numerous applications such as health, security, authentication system, recruitment, and also in intelligent social robots. Convolutional Neural Network (CNN) has recently shown excellent performance in analysing human face images and videos. This paper proposed an age group classification task using CNN that trained and tested with an All-Age Face (AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The comparison result with related research is shown in Table 3. Furthermore, the results of this study have been compared to previous research [27] using the same model but using a different dataset of All-Age Face (AAF) datasets in different amounts of data. In addition, there are also similarities in terms of data splitting methods that use the hold out method but with different amounts on each section.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison result with related research is shown in Table 3. Furthermore, the results of this study have been compared to previous research [27] using the same model but using a different dataset of All-Age Face (AAF) datasets in different amounts of data. In addition, there are also similarities in terms of data splitting methods that use the hold out method but with different amounts on each section.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there are also similarities in terms of data splitting methods that use the hold out method but with different amounts on each section. Mustapha et al [27] proposed an age group classification to address the issue of class imbalance in CNN-based classifications. Although there is a large difference in the number of datasets, the performance in terms of accuracy varies only marginally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessments were made on sketch classification performance and gender verification accuracy based on how many images were taken from each individual. Demographic variables such as categorization, age, ethnicity, and gender have a significant impact on the appearance of the human face, with each category further subdivided into classes such as black and white, male and female, young (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), middle age (30-50), and old (50-70). Most students look more like their peers in their age group than they do those in other age groups.…”
Section: Existing Methodsmentioning
confidence: 99%
“…Race recognition (RR), which has numerous applications in surveillance systems, image and video interpretation, analysis, and others, is a challenging problem to solve. The use of a deep-learning model to help solve that challenge has been analyzed in [28,29]. A race recognition framework (RRF) was proposed, which included an information collector (IC), face detection and preprocessing (FD&P), and RR modules.…”
Section: Existing Methodsmentioning
confidence: 99%